2017
DOI: 10.1038/ncomms14630
|View full text |Cite
|
Sign up to set email alerts
|

Administration of nucleoside-modified mRNA encoding broadly neutralizing antibody protects humanized mice from HIV-1 challenge

Abstract: Monoclonal antibodies are one of the fastest growing classes of pharmaceutical products, however, their potential is limited by the high cost of development and manufacturing. Here we present a safe and cost-effective platform for in vivo expression of therapeutic antibodies using nucleoside-modified mRNA. To demonstrate feasibility and protective efficacy, nucleoside-modified mRNAs encoding the light and heavy chains of the broadly neutralizing anti-HIV-1 antibody VRC01 are generated and encapsulated into lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
261
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 285 publications
(273 citation statements)
references
References 45 publications
2
261
0
1
Order By: Relevance
“…It conferred full protection against intoxication and virus challenge and could eradicate neoplastic cells in a murine tumor model. While the present manuscript was under review, the feasibility of using mRNA for passive vaccination was independently confirmed in an HIV model (Pardi et al , ).…”
Section: Discussionmentioning
confidence: 79%
“…It conferred full protection against intoxication and virus challenge and could eradicate neoplastic cells in a murine tumor model. While the present manuscript was under review, the feasibility of using mRNA for passive vaccination was independently confirmed in an HIV model (Pardi et al , ).…”
Section: Discussionmentioning
confidence: 79%
“…Two early reports demonstrated that dendritic cells (DCs) electroporated with mRNAs encoding antibodies against immuno-inhibitory proteins secreted functional antibodies and improved immune responses in mice 195,196 . Three recent publications have described the use of injectable mRNA for in vivo production of therapeutic antibodies: Pardi and colleagues demonstrated that a single intravenous injection into mice with lipid nanoparticle (LNP)-encapsulated nucleoside-modified mRNAs encoding the heavy and light chains of the anti-HIV-1 neutralizing antibody VRC01 rapidly produced high levels of functional antibody in the serum and protected humanized mice from HIV-1 infection 197 ; Stadler and co-workers demonstrated that intravenous administration of low doses of TransIT (Mirus Bio LLC)-complexed, nucleoside-modified mRNAs encoding various anticancer bispecific antibodies resulted in the elimination of large tumours in mouse models 198 ; and Thran and colleagues 199 utilized an unmodified mRNA–LNP delivery system 12 to express three monoclonal antibodies at levels that protected from lethal challenges with rabies virus, botulinum toxin and a B cell lymphoma cell line. No toxic effects were observed in any of these studies.…”
Section: Discussionmentioning
confidence: 99%
“…6). While the group of Drew Weissman described successful passive mRNA immunization for prophylaxis of viral infections [267], Stadler et al demonstrated the applicability of mRNA-mediated antibody expression for cancer immunotherapy [264]. The feasibility of using mRNA for such indications was confirmed by Thran et al who applied different mRNAencoded antibody formats to diverse biological threats, viruses, toxins, and tumors [268].…”
Section: Antibody Therapy With Mrnamentioning
confidence: 99%